Gambir (Uncaria gambir Roxb.) as A Potential Alternative Treatment for Hyperlipidemia - Nanang Yunarto; Novi Sulistyaningrum; Arifayu Addiena Kurniatri; Berna Elya (Media Penelitian dan Pengembangan Kesehatan, 2021)
Gambir (Uncaria gambir Roxb.) is a member of family of Rubiaceae. In Asia including Indonesia, extracts of gambir are empirically used daily to weed out. The high content of catechin flavonoids in gambir has a pharmacological effect in the treatment of hyperlipidemia that potential to be developed into traditional medicine. This literature review aimed to examine the potency of pharmacological effect of gambir as hyperlipidemia treatment therapy based on the results of studies in silico, in vitro, in vivo pharmacological effects and its safety to provide evidence of scientific information to the community. The literatures used for analysis in this study including evidence-based articles on both pharmacology and safety which are available in Pubmed and Google Scholar. The results showed a very strong potency of gambir plants in the treatment of hyperlipidemia with catechin as bioactive compounds. In silico study revealed mechanism action of catechin as antihyperlipidemic using 2 pathways, inhibition of the enzyme HMG-CoA reductase and increase the LDL receptors. In vitro studies of catechin are able to inhibit lipid absorption in the intestine through inhibition of pancreatic lipase activity, lipid hydrolysis and emulsification, micelle cholesterol deposition. Pre-clinical tests on animals showed that the ethyl acetate fraction of gambir leaves was able to reduce the levels of total cholesterol, triglycerides, LDL and increase blood plasma HDL. The long-term use of gambir leaves has been proven to be safe, not mutagenic, no hematological, clinical biochemical abnormalities and no abnormalities in the vital organs of the animal models. Abstrak Gambir (Uncaria gambir Roxb) adalah tumbuhan perdu dari suku Rubiaceae. Di Asia termasuk Indonesia, secara empiris ekstrak gambir digunakan sehari-hari untuk menyirih. Kandungan flavonoid katekin yang tinggi dalam gambir memiliki efek farmakologi dalam pengobatan hiperlipidemia yang berpotensi untuk dikembangkan menjadi obat tradisional. Kajian literatur ini bertujuan untuk mengkaji potensi farmakologi gambir sebagai terapi pengobatan hiperlipidemia berdasarkan hasil studi efek farmakologi in silico, in vitro, in vivo efek farmakologi dan keamanannya, sehingga memberikan bukti informasi ilmiah kepada masyakarat. Literatur yang digunakan dalam proses review meliputi literatur dengan berbasis bukti baik farmakologi maupun keamanan yang tersedia di Pubmed dan Google Scholar. Hasil kajian menunjukkan potensi yang sangat kuat dari tanaman gambir dalam pengobatan hiperlipidemia dengan katekin sebagai senyawa bioaktif utama. Studi in silico menunjukkan mekanisme aksi katekinsebagai antihiperlipidemia menggunakan dua jalur yaitu penghambatan enzim HMG-CoA reduktase dan peningkatan reseptor LDL. Studi in vitro katekin mampu menghambat penyerapan lipid di usus melalui penghambatan aktivitas lipase pankreas, hidrolisis lipid dan emulsifikasi, serta pengendapan kolesterol misel. Studi in vivo menunjukkan fraksi etil asetat daun gambir mampu menurunkan kadar kolesterol total, trigliserida, LDL dan meningkatkan HDL plasma darah. Penggunaan daun gambir dalam jangka panjang terbukti aman, tidak mutagen, tidak ditemukan kelainan hematologi, biokimia klinis dan tidak menyebabkan kelainan organ vital hewan uji.